PEMELIHARAAN KESEHATAN GIGI DAN MULUT DI MASA PANDEMI COVID-19 PADA ORANG TUA ANAK BERKEBUTUHAN KHUSUS - Marie Louisa; Johan Arief Budiman; Trijani Suwandi; Sariyani Pancasari Audry Arifin (Universitas Trisakti, 2021)
Special Needs Children cannot carry out daily activities normally so they need help from others around them, such as parents, family members, caregivers, or teachers at school. Due to limitations in terms of cognitive, psychomotor, and affective in special needs children, training program will be more effective if it is given to their assistants (parents and teachers). These training targets for maintaining dental and oral health are parents and teachers of special needs children at SLB C Dian Kusuma. The training program is equipped with a video demonstration, conducted online using the Zoom application held on July 30, 2020, with a team consisting of 4 lecturers and 4 clinical students of the Faculty of Dentistry, Universitas Trisakti followed by 30 participants. Participants' knowledge was assessed by pretest and posttest using Google Form. The results of training on maintaining dental and oral health for parents and teachers of special needs children at SLB C Dian Kusuma which were conducted through webinars showed satisfactory results. The mean score of the pretest was 77+22.53 and the mean value of the posttest was 98+11.99. There was an increase in the posttest scores of the extension participants by 22% with changes in the increase in the correct answers percentage from the pre-posttest ranging from 6.6%-45%.